2017
DOI: 10.3892/mmr.2017.6605
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells in infectious disease

Abstract: Regulatory B cells (Bregs) are a subset of B cells, which reportedly exert significant immunomodulatory effects through the production of interleukin (IL)-10, IL-35 and transforming growth factor-β. Over the last decade, studies have indicated that Bregs function in autoimmune and allergic diseases through antigen-specific and non-specific immunoregulatory mechanisms. However, only a limited number of reviews have focused on the role of Bregs during infection, particularly their functions in intracellular infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 55 publications
0
46
0
1
Order By: Relevance
“…This regulatory function is associated with their production of anti‐inflammatory cytokines, such as IL‐35, TGF‐β and, in particular, IL‐10 . Previous studies have shown that Breg cells, through the production of IL‐10, suppress pathogenic T cells and inhibit autoimmune inflammatory diseases such as arthritis, experimental autoimmune encephalomyelitis (EAE) and colitis, as well as contact hypersensitivity . Moreover, Breg cell transfer can effectively reverse autoimmune diseases in murine models, such as mice with experimental collagen‐induced arthritis (CIA) and lupus‐prone mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulatory function is associated with their production of anti‐inflammatory cytokines, such as IL‐35, TGF‐β and, in particular, IL‐10 . Previous studies have shown that Breg cells, through the production of IL‐10, suppress pathogenic T cells and inhibit autoimmune inflammatory diseases such as arthritis, experimental autoimmune encephalomyelitis (EAE) and colitis, as well as contact hypersensitivity . Moreover, Breg cell transfer can effectively reverse autoimmune diseases in murine models, such as mice with experimental collagen‐induced arthritis (CIA) and lupus‐prone mice .…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous studies have shown that Breg cells, through the production of IL-10, suppress pathogenic T cells and inhibit autoimmune inflammatory diseases such as arthritis, experimental autoimmune encephalomyelitis (EAE) and colitis, as well as contact hypersensitivity. [3][4][5] Moreover, Breg cell transfer can effectively reverse autoimmune diseases in murine models, such as mice with experimental collagen-induced arthritis (CIA) and lupus-prone mice. 6,7 However, the current understanding of the mechanisms of Breg expression and production of IL-10 remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the regulatory role of B cells was recently described in different diseases and immune conditions, including autoimmunity (1), allergy (2), cancer (3), and infection (4). However, B cells can also modulate the function of other immune cells by producing cytokines or presenting antigens.…”
Section: Introductionmentioning
confidence: 99%
“…However, B cells can also modulate the function of other immune cells by producing cytokines or presenting antigens. In particular, the regulatory role of B cells was recently described in different diseases and immune conditions, including autoimmunity (1), allergy (2), cancer (3), and infection (4). Regulatory B cells (Breg) have been shown to induce regulatory T cells (Treg) (5) and modulate effector T cell functions by suppressing proliferation (6), cytokine production by stimulated CD4+ T cells (7), and differentiation of Th1 and Th17 cells (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Moreover, IL-35 and TGF-β have also been associated with B cellmediated immunosuppression in Salmonella infection in mice. 30 In fact, via IL-10, Bregs may also have a role in infectious diseases, particularly with respect to viral infections such as HIV and hepatitis B virus (HBV). In HBV, Bregs regulate antigen-specific CD8 + T cells during HBV infection.…”
mentioning
confidence: 99%